Մասնավոր հատվածում կաշառակերության հարցի շուրջ - Ա. Ժ. Այվազյան (ՀՀ ԳԱԱ հրատ.)
С целью обеспечения требований одного из основополагающих принципов уголовного законодательства–принципа индивидуализации справедливости и ответственности предлагается внести изменения в диспозиции преступлений, связанных с коррупцией участников и организаторов профессиональных спортивных соревнований и показательных коммерческих конкурсов (УК статья 201). To meet the requirements of one of the fundamental principles of the criminal legislation, i.e. the principle of individualization of justice and accountability, it is suggested that amendments should be introduced into the disposition of crimes related to corruption, professional sports competition participants and organisers, as well as those of commercial expositions (Article 201 of the Criminal Code).
Keywords: Law